Morfologia da germinação de sementes e crescimento in vitro de Cattleya walkeriana Gardner em diferentes meios nutritivos - Galdiano, Renato Fernandes [UNESP]; Mantovani, Cibele [UNESP]; Gomes, Elisângela Soares [UNESP]; Gasparino, Eduardo Custódio [UNESP]; Moro, Fabíola Vitti [UNESP]; De Macedo Lemos, Eliana Gertrudes [UNESP] (My University, 2014)
The aim of this work was to analyze the early seedling development and in vitro growth of Cattleya walkeriana under different culture media in order to improve the process of propagation of this species. Seedlings 90-day old ((0,8 ± 0,1 cm of length) were transferred into culture media Vacin & Went, WPM, Knudson-C, Phytamax® and 1/2 MS. After 90 days, biometric characteristics of shoot length, root number, width of largest root and fresh weight were evaluated and means separated by Tukey's test at 5%. Cattleya walkeriana embryo yields from seed micropylar end a conical chrolophilated structure denominated protocorm 30-day after sowing. At 60 days after sowing, protocorm develops leaflets at upper portion, and rhizoids in the lower. 1/2 MS culture medium favored in vitro growth and can be recommended for the production of Cattleya walkeriana.
Seed germination morphology, and in vitro growth of Cattleya walkeriana Gardner under different culture media
Keywords: In vitro germination; Native orchid; Protocorm